`Boy!': The Hinge of Colonial Double Talk - Anne M. Menke (Studies in 20th & 21st Century Literature, 1991)
The French colonial enterprise in Africa enforced racial segregation, yet encouraged Africans to assimilate the French language, culture, and religion. The essay questions these contradictory policies through readings of Ferdinand Oyono's novels. It argues that a figure that embodies undecidability—the colonial servant known as the "boy"—is the locus of the denaturalization of the identities that were simultaneously institutionalized and denied by the Manichaean colonial world.
Keywords: French colonial; Africa; racial segregation; race; Africans; French language; culture; religion; policies; Ferdinand Oyono; embodies; undecidability; colonial servant; servant; boy; locus; denaturalization of the identities; identity; institutionalized; denied; Manichaean colonial world; colonial; colonialism; Manichaean